New directions in theorizing qualitative research indigenous research - Denzin, Norman K.; Salvo, James (New Directions for Theorizing in Qualitative Inquiry Consists of Thematic Edited Volumes That Help Us Understand How to Put Qualitative Inquiry Into Practice. The Chapters in Each Volume, From Established and Emerging Scholars, Represent New Directions Fo, v. 4 Authors, 2020)
The chapters in this volume collect together perspectives on Indigenous epistemologies. These Indigenous ways of knowing pay particular attention to the relational aspects of language, culture, and place. They are not identified as specific themes, but as integrated parts of a philosophy, for Indigenous epistemologies think within a relational framework, so that all aspects are best understood from this perspective. Indigenous ways of knowing have resisted colonization and oppression, and as such, Indigenous research perspectives exemplify a commitment to social justice, one that recovers knowledges that have been silenced or subjugated. When such knowledge is shared, we can see how to challenge oppressive regimes. We can see how to seek truth in a relational way that's attendant to being together. Indigenous Research takes up issues of social justice in a way that is informed by Indigenous epistemologies, an important practice in contemporary research, particularly qualitative inquiry.